PARTISIPASI PEREMPUAN DALAM PEMBANGUNAN DESA STUDI DI DESA GIRI PURNO KECAMATAN RIMBO ILIR KABUPATEN TEBO - Miranti Miranti; Putut Haryanto (GOVERNANCE: Jurnal Ilmiah Kajian Politik Lokal dan Pembangunan, 2021)
This research was conducted in Giri Purno Village, Rimbo Ilir District, Tebo Regency. The location of the research will be carried out in Giri Purno Village, Rimbo Ilir District, Tebo Regency. This location was chosen "purposively" that is intentionally. Considering the condition of the area which shows the low level of women's participation in the development of Giri Purno Village in terms of village consultations, formulation, planning and implementation of development. The method used in this study is a descriptive method with a qualitative approach, which intends to find out and get an overview of the problems that occur at a certain place and time. Forms of Women's Participation in the Development Process of Giri Purno Village, Rimbo Ilir District, include: 1. Non-Physical Participation (Ideas / Thoughts) and 2. Participation in the Form of Energy. Factors Encouraging Women's Participation in the Giri Purno Village Development Process: Awareness / Willing Factors, Educational Factors, Income factor / Income. The inhibiting factors for women's participation in the development of Giri Purno Village include the busyness of women, lack of communication and external factors, namely the government leadership factor